Strategi Pemanfaatan Instagram Sebagai Media Komunikasi Pemasaran Digital Yang Dilakukan Oleh UMKM Bolen Kharinda - Dian Candra Dewi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
The development of marketing communications today is not only done in the conventional course. Marketers now also take advantage of new media like the Internet as an alternative to approach prospective customers. Digital marketing is a marketing activity that uses the Internet and information technology to expand and improve the functions of traditional marketing. In carrying out marketing communications, companies must have a strategy so that all predetermined plan can be achieved. A good strategy will benefit the company as the realization of the goals of the company. This study discusses the utilization strategy of Instagram as a digital marketing communications media conducted by Bolen Kharinda. The method used in this research is descriptive qualitative method. In addition, this study also used in-depth interviews technique, literature studies and documentation. Based on the results of the research and discussion, it is known that the planning of Instagram utilization that have been done by Bolen Kharinda are to analyze the problem, analyze the audience, determine the destination, the selection of media and communication channels, and develop plans or projects to achieve objectives. The implementation of Instagram utilization by Bolen Kharinda are the use of features available in Instagram such as upload photos, videos and reels, comments, hashtags, caption, tagging, and Instagram Ads for social media maintenance and also followers and like for social media endorsement. Evaluation of Bolen Kharinda’ Instagram utilization is the result of increased sales and successfully to open branch store and outlets in Tuban City.